Detection of gene clusters for biodegradation of alkanes and aromatic compounds in the Rhodococcus qingshengii VKM Ac-2784D genome - Yu. A. Markova; I. S. Petrushin; L. A. Belovezhets (Вавиловский журнал генетики и селекции)
Bacterial species of the genus Rhodococcus are known to be efficient degraders of hydrocarbons in contaminated soil. They are also employed for bioremediation of polluted environments. These bacteria are widely met in soil, water and living organisms. Previously, we have isolated the Rhodococcus qingshengii strain VKM Ac-2784D from the rhizosphere of couch grass growing on oil-contaminated soil. This strain can effectively degrade oil and some model compounds (naphthalene, anthracene and phenanthrene). The results of phylogenetic analysis show that this strain belongs to the species R. qingshengii. To understand the catabolic properties of this strain, we have studied its gene clusters possessing such properties. The alkane destruction genes are represented by two clusters and five separate alkB genes. The destruction of aromatic compounds involves two stages, namely central and peripheral. The R. qing shengii VKM Ac-2784D genome contains four out of eight known central metabolic pathways for the destruction of aromatic compounds. The structure of the gene clusters is similar to that of the known strains R. jostii RHA1 and R. ru ber Chol-4. The peripheral pathways include the genes encoding proteins for benzoic acid destruction. The presence of biphenyl 2,3-dioxygeneses as well as gene clusters of benzoate and 2-hydroxypentandienoate pathways suggests that R. qingshengii VKM Ac-2784D could degrade polychlorinated biphenyls. The biodegradation ability can be enhanced by biosurfactants, which are known to be synthesized by Rhodococcus. The R. qingshengii VKM Ac-2784D genome contains the otsA, otsB, treY, treZ genes. The bioinformatics data are supported by the previous biochemical experiments that allow a mixture of species with a wide variation of metabolic pathways to be obtained.